2016
DOI: 10.1080/00918369.2016.1172869
|View full text |Cite
|
Sign up to set email alerts
|

Different Dimensions: Internalized Homonegativity Among African American Men Who Have Sex With Men in the Deep South

Abstract: This study examined the psychometric properties of the Internalized Homonegativity Inventory (IHNI) among African American men who have sex with men (AAMSM) in the southeastern United States. Data from 261 AAMSM were analyzed using exploratory factor analysis. Results showed evidence of a two-factor solution: personal and moral homonegativity and gay affirmation. Internal consistencies were greater than .80, and correlations with other variables (e.g., sociodemographics, religiosity, masculinity) provided evid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…In addition, to our knowledge, no studies have employed GPS methods among MSM in the Deep South, including among Black MSM in the Deep South. Emerging research has shown that Black MSM in the Deep South may be different than MSM in other geographies, particularly in terms of levels of internalized homophobia and willingness to disclose sexual identity and/or behavior [2831], and these concerns about privacy may influence one’s desire to participate in GPS-related research [32]. An in-depth assessment of the neighborhood contexts of daily life among Black MSM may be particularly important as emerging research has shown that Black MSM exhibit higher degrees of discordance between common neighborhood contexts (e.g., where individuals reside, socialize, or have sex) than White MSM [1921].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, to our knowledge, no studies have employed GPS methods among MSM in the Deep South, including among Black MSM in the Deep South. Emerging research has shown that Black MSM in the Deep South may be different than MSM in other geographies, particularly in terms of levels of internalized homophobia and willingness to disclose sexual identity and/or behavior [2831], and these concerns about privacy may influence one’s desire to participate in GPS-related research [32]. An in-depth assessment of the neighborhood contexts of daily life among Black MSM may be particularly important as emerging research has shown that Black MSM exhibit higher degrees of discordance between common neighborhood contexts (e.g., where individuals reside, socialize, or have sex) than White MSM [1921].…”
Section: Introductionmentioning
confidence: 99%
“…While the original IHNI measured internalized homonegativity across three subscales ("Personal Homonegativity," "Gay Affirmation," "Morality of Homosexuality"), an exploratory factor analysis of SHIFT Study data provided evidence of a two-factor solution; in the exploratory factor analysis, one factor included all of the items from both the "Personal Homonegativity" and "Morality of Homosexuality" subscales, while the "Gay Affirmation" subscale remained intact. The "Gay Affirmation" label was retained, while the combined factor was reclassified as "Personal/Moral Homonegativity" (Smallwood, Spencer, Annang Ingram, Thrasher, & Thompson-Robinson, 2013). The two-dimensional conceptualization of internalized homonegativity was used in the present study.…”
Section: Methodsmentioning
confidence: 99%
“…Prior research on homonegativity among Black GBMSM has primarily focused on internalized homonegativity and is generally not specific to younger subsets of this population. Of note, studies in primarily white samples may not reflect the lived experiences of YB-GBMSM, as researchers have shown marked differences in amount and characterizations of internalized homonegativity across racial groups [13][14][15]. Studies specific to Black GBMSM have identified higher self-perceived masculinity and increased levels of religiosity as risk factors for internalized homonegativity [13].…”
Section: Introductionmentioning
confidence: 99%